Pemodelan Kemisikinan di Indonesia dengan Generalized Method Momment Arellano dan Bond - Arya Fendha Ibnu Shina (Universitas Bumigora, 2019)
Poverty is one of the important indicators to see the success of a country's development. Every country will try optimally to reduce poverty. On the other hand poverty is one of the economic variables that is dynamic, meaning that the value of a variable is influenced by the value of other variables and also the value of the variables concerned in the past. The purpose of this study was to analyze the effect of lag from poverty indicators, GDP, Gini Index, HDI, and on poverty levels. Based on the results of the study concluded that the lag coefficients of poverty and HDI indicators significantly influence the poverty of provinces in Indonesia. In addition, if there is an increase in HDI of 1% then in the short term it will cause a decrease in poverty of 1.747% and in the long term of 2.085